MicroRNA expression profile in plasma from type 1 diabetic patients: Case-control study and bioinformatic analysis - Assmann, Taís S.; Recamonde-Mendoza, Mariana; Puñales, Márcia; Tschiedel, Balduíno; Canani, Luís H.; Crispim, Daisy (Diabetes research and clinical practice, 2018)
To investigate a miRNA expression profile in plasma of type 1 diabetes (T1DM) patients and control subjects and analyze the putative pathways involved. Expressions of 48 miRNAs were analyzed in plasma of 33 T1DM patients and 26 age-and-gender-matched controls using Stem-loop RT-PreAmp PCR and TaqMan Low Density Arrays (Thermo Fisher Scientific). Five dysregulated miRNAs were then chosen for validation in an independent sample of 27 T1DM patients and 14 controls, using RT-qPCR. Bioinformatic analyses were performed to determine in which pathways these miRNAs are involved. Nine miRNAs were differentially expressed between recently-diagnosed T1DM patients (<5 years of diagnosis) and controls. No differences were observed between patients with ≥5 years of diagnosis and controls. After validation in an independent sample of T1DM patients, miR-103a-3p, miR-155-5p, miR-200a-3p, and miR-210-3p were confirmed as being upregulated in recently-diagnosed T1DM patients compared with controls or patients with ≥5 years of diagnosis. Moreover, miR-146a-5p was downregulated in recently-diagnosed T1DM patients compared with the other groups. These five miRNAs regulate several genes from innate immune system-, MAPK-, apoptosis-, insulin- and cancer-related pathways. Five miRNAs are dysregulated in recently-diagnosed T1DM patients and target several genes involved in pathways related to T1DM pathogenesis, thus representing potential T1DM biomarkers.